2016
DOI: 10.1080/00324728.2016.1254813
|View full text |Cite
|
Sign up to set email alerts
|

Shifting racial hierarchies: An analysis of residential segregation among multi-racial and mono-racial groups in the United States

Abstract: Multi-racial (mixed-race) people constitute a growing percentage of the United States (US) population. The study reported in this paper used residential segregation measures as a proxy for social distance, to examine whether segregation levels of multi-racial groups differ from those of mono-racial groups in the US in 2010. First, we find that all multi-racial groups considered in the study experience lower levels of segregation at county level than their mono-racial counterparts. However, black-whites and His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Asian-White children are much more likely to live in suburban homeowner spaces in areas that are predominantly White compared to their monoracial counterparts (Alba 2020). Furthermore, Asian and White segregation is at 41, while Asian-White and White segregation is at 21 (Kwon and Kposowa 2017). Similar trends are found in educational attainment.…”
Section: The Debate Over Assimilation and Movement In The Racial Hier...supporting
confidence: 69%
See 1 more Smart Citation
“…Asian-White children are much more likely to live in suburban homeowner spaces in areas that are predominantly White compared to their monoracial counterparts (Alba 2020). Furthermore, Asian and White segregation is at 41, while Asian-White and White segregation is at 21 (Kwon and Kposowa 2017). Similar trends are found in educational attainment.…”
Section: The Debate Over Assimilation and Movement In The Racial Hier...supporting
confidence: 69%
“…The complexity of racial identity is highlighted. On the one hand, the participants report certain indicators of assimilation or closeness to Whiteness for Asian Americans and Asian-White multiracials, such as skin tone, education, and other markers of socioeconomic (Alba 2020;Bonilla-Silva 2006;Glen 2009;Iceland and Nelson 2010;Kwon and Kposowa 2017), which at a quick glance, fit the structural factors associated with being "honorary Whites". Yet, as Chong and Song (2022, p. 2) argue, this framing of Asian-Whites as close to Whiteness is based on a "white racial frame", where Asian Americans are understood as a "compliant, upwardly mobile "model minority", suitable for absorption into the White racial majority through interracial marriage" and desiring to be White.…”
Section: At a Glance: Structural Indicators Of Movement Into Whitenessmentioning
confidence: 99%
“…For example, not only does previous research indicate that high observed educational attainment for Asian Americans does not necessarily hold across all national-origin groups (Vartanian et al, 2007 ), there also is evidence of a sharp divide in socioeconomic outcomes between foreign-born and U.S.-born Black Americans with significantly higher levels of educational attainment among Black immigrants (Hamilton, 2014 , 2020 ; Waters et al, 2014 ). Other research highlights that conclusions about the racial hierarchy can also vary according to immigrant generation (Kim, 2015 ), deportation status (Rugh, 2020 ), and region (Kwon & Kposowa, 2017 ). As scholars continue to study the racial hierarchy, it will be important to heed calls to attend to these dimensions of intra-group heterogeneity (Ford & Harawa, 2010 ; Jiménez et al, 2015 ) and to be mindful about how methodological decisions affect the research process and, ultimately, knowledge production.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research suggests that multi-racial people are generally less segregated than mono-racial people, but segregation increases as the percentages of other races/ethnicities in an area increase. 20 Thus, we would expect the outcomes of multi-racial people in this study to be dependent on the level of segregation in a county.…”
Section: A Statistical Model Of Us Migration and Oods By Race/ethnicitymentioning
confidence: 94%